KEPERLUAN ZIKIR DALAM PEMBELAJARAN MENURUT MANUSKRIP MELAYU: KAJIAN TERHADAP MSS 2906 (B) TIBYÄ€N AL-MARÄ€M (The Importance of Dhikr in Learning According to Malay Manuscript: A Study on MSS 2906 (B) TibyÄn al-MarÄm) - Mamat, Mohd Anuar; Mohd Zarif, Muhammad Mustaqim (Journal of Al-Tamaddun, 2019)
Dhikr is a devotional act in Islam that is laden with various benefits as mentioned in the Holy Quran and hadith. This article reviews the importance of dhikr in learning based on a rare Malay work titled Tibyān al-Marām Ṭalibah al-Ṭalabah (MSS 2906B). From the codicological perspective, this manuscript originated from Aceh and was written in Jawi script in a period between the end of 18th and early 19th century. It is a Malay translation and adaptation of the Arabic text titled Ṭalibah al-Ṭalabah fī Ṭarīq al-‘Ilm li man Ṭalabah by Sadīd al-Dīn Muḥammad al-Kāshgharī (m.705H). At present, the manuscript is kept at the National Centre for Malay Manuscripts, National Library of Malaysia. This article finds that dhikr is greatly encouraged to be practiced by all, especially students as it provides great spiritual benefits for them and helps to improve their memory and increase their rizq (provision). There are also various types of dhikr and prayers described in this manuscript as guidance for students. The discussion of this topic is in line with the previous works on the ethics and rules of conduct for students (adab al-muta‘allim) based on the Islamic educational tradition.